2004
DOI: 10.1159/000081003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Tumorous Associated Antigen Sialyl-Tn Expression and ST6GalNAc I Activity in Human Colon Adenocarcinoma

Abstract: Objectives: Sialyl-Tn (sTn) is a mucin carbohydrate-associated antigen that is strongly expressed in a large number of colorectal carcinomas. In this study, we combined immunohistochemical and enzymatic techniques in order to find the correlation between sTn tissue expression and the sialyltransferase activity (ST6GalNAc I) responsible for its synthesis in colorectal cancer (CRC) patients. Methods: We compared sTn expression in healthy (n = 46), tumorous (n = 60) and transitional tissue (n = 46) from CRC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
4
22
1
Order By: Relevance
“…Our findings are in contrast to the data relating to the appearance of STn in colon cancers, where no correlation was found between the activity of ␣2,6-sialyltransferase(s) adding sialic acid to GalNAc and STn expression in cancer tissues (32). The explanation for the apparent de novo expression of STn in colon cancer relates to a modification of the sialic acid in the cells of normal colonic tissues.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are in contrast to the data relating to the appearance of STn in colon cancers, where no correlation was found between the activity of ␣2,6-sialyltransferase(s) adding sialic acid to GalNAc and STn expression in cancer tissues (32). The explanation for the apparent de novo expression of STn in colon cancer relates to a modification of the sialic acid in the cells of normal colonic tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…One obvious mechanism is an increase in the level of activity of the enzyme(s), which adds sialic acid to GalNAc. Studies in colon carcinoma have demonstrated that this is not the case in this malignancy (32), because the level of ␣2,6-sialyltransferase enzyme activity is similar in normal and cancerous colonic tissue, whereas STn is only detectable in the cancers. The difference in colon carcinoma appears to be due to a lack of detection of the STn on most normal tissue, because of a modification of the sialic acid resulting in it not being recognized by the STn-specific antibodies.…”
mentioning
confidence: 98%
“…Thus, both PSA and NCAM molecules show a low constitutive expression in control tissue and undergo a statistically significant overexpression in tumor tissue from CRC patients. This type of response is in accordance with those exhibited by other sialylated epitopes in CRC [47,48], but disagrees with previous findings about the presence of NCAM in CRC [34,49]. Roesler et al [34] reported the profile of expression of the 180-kDa NCAM isoform in control and tumor tissue from 15 CRC patients, as well as the association of decreased NCAM expression with poor prognosis.…”
Section: Discussionsupporting
confidence: 42%
“…This enzyme, ST6GalNAc-II, was also shown to have some specificity in vitro for GalNAc substrates O-linked to proteins (Tn antigen). Moreover, a lack of concordance observed between ST6GalNAc-I and STn expression in gastric carcinomas has been observed in colorectal carcinomas, 42 and it is known that cell lines and tissues lacking STn may still show low levels of ST6GalNAc-I mRNA, 43 indicating that alternative biosynthetic mechanisms may be at play.…”
Section: Cdx2 Regulates St6galnac-i In Intestinal Metaplasia R Pinto mentioning
confidence: 99%